Parasitic pneumonia caused by Paragonimus spp. in a wild Royal Bengal Tiger, Mysuru, South India - Dharanesha, N. K. (J Parasit Dis, 2019)
Parasitic pneumonia induced by genus Paragonimus involves many species, which affects both humans and animals and it is a food borne zoonotic disease. In this report, we have described the gross and histopathological findings of Paragonimus fluke infection in lungs of tiger. The postmortem examination of sub adult male wild tiger (Panthera tigris tigris) died in captivity was conducted, earlier which was rescued by Forest Department, Mysuru, Karnataka, India. External examination of carcass revealed pale oral and conjunctival mucous membranes with sunken eye balls. During necropsy, moderate congestion, consolidation and numerous transparent to dark encysted lesions were found in the parenchyma of all lobes of lungs visible grossly on pleural surface. Lungs were hemorrhagic with necrotic foci around the cysts. The incision of encysted lesions revealed the presence of flukes (2–3 in numbers) in each cyst with brownish exudate. The lung tissues with lesions were collected in 10% formalin and haematoxylin and eosin staining was done for histopathological evaluation. The flukes were identified as Paragonimus spp. based on the morphology and micrometry. The histopathological examination revealed presence of longitudinal sections of flukes in bronchial lumen (in pair) with tegument and tegumental spines surrounded by connective tissue capsule as cystic encapsulation and numerous eggs in adjacent lung parenchyma. Necrosis and moderate fibrosis of lung parenchyma with infiltration of polymorphonuclear and mononuclear inflammatory cells were observed around fluke as well as eggs. The squamous cell metaplasia of lining bronchial epithelium and atelectasis of alveoli were also prominently seen.